Effect of Probiotic Supplementation on Sprague Dawley Rat Liver Histopathology Fed by High Fat High Fructose Diet - Kusumawati, Ninung Rose Diana; Panunggal, Damianus Galih; Mexitalia, Maria; Sidhartani, Magdalena; Pratiwi, Juwita; Utari, Agustini (Journal of Biomedicine and Translational Research, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) is an important cause of liver disease burden worldwide. The gastrointestinal microbiota has a close relationship with the liver as the liver is most exposed to intestinal bacteria. Microbial manipulation is a potential and effective therapy as an alternative in the management of NAFLD/NASH. It has been found that probiotics prevent NAFLD/NASH. However, the study about the protective effect of probiotics on NAFLD/NASH is still limited. Objective: The objective of this study is to evaluate the effect of probiotics on liver histopathology Sprague Dawley rats which given high-fat high fructose (HFHFr) dietMethods: This study is a murine-model post-test-only control study group design. The samples were 21 Sprague Dawley male rats in 7 – 8 weeks of age and were divided into three groups. The Control Group (C) was provided with a standard chow diet for eight weeks. The Non-Probiotic (NP) group was given a High-Fat High Fructose (HFHFr) diet for eight weeks. The Probiotic group (P) was given a HFHFr diet for eight weeks, and a combination of HFHFr and probiotic supplementation consisted of Lactobacillus acidophilus, Bifidobacterium longum, and Streptococcus thermophilus for the next eight weeks. Histopathological samples were obtained from liver biopsy to assess steatosis, NAFLD activity score (NAS), and fibrosis stages. Wilcoxon test was done to analyze body weight before and after treatment. We analyzed the difference in histopathological results using the Mann-Whitney test.Results: We found a significant difference in NAFL and NAS Score between NP and P group. The P group was shown to have lower trends for NAFLD and NASH than the NP group, but not for fibrosis. There is no significant difference between pre and post-test body weight. Conclusion: Probiotics supplementation has a protective effect on liver histopathology against disturbances caused by the HFHFr diet.